Sectoral Booms and Misallocation of Managerial Talent : Evidence from the Chinese Real Estate Boom - Shi, Yu (IMF Working Papers; Working Paper ;, 2018)
This paper identifies a new mechanism leading to inefficiency in capital reallocation at the extensive margin when an economy experiences a sectoral boom. I argue that imperfections in the financial market and capital barriers to entry in the booming sector create a misallocation of managerial talent. Using comprehensive firm-level data from China, I first provide evidence that more productive firms reallocate capital to the booming real estate sector, and demonstrate that the pattern is likely driven by fewer financial constraints on these firms. I then use a structural estimation to verify the talent misallocation. Finally, I calibrate a dynamic model and find that the without the misallocation, the TFP growth in the manufacturing sector would have improved by 0.5% per year.